Morphology and taxonomic significance of the labrum in the flea beetle genus Chaetocnema Stephens, 1831 (Coleoptera, Chrysomelidae, Galerucinae, Alticini) - Mathew, Sandra Maria; Prathapan, K. D. (Zootaxa, 2024)
The structure of labrum or upper lip in adult Coleoptera is only minimally investigated and used in classification and phylogeny. This study investigates the morphology of the labrum in the flea beetle genus Chaetocnema Stephens, 1831 (Chrysomelidae, Galerucinae, Alticini) to assess and develop a terminology and identify potential morphological characters useful to delimitation of species and species groups as well as phylogeny reconstruction in leaf beetles.